2020
DOI: 10.5213/inj.2040154.077
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Glycyrrhizic Acid on Scopolamine-Induced Cognitive Impairment in Mice

Abstract: Purpose: Cognitive impairment is one of the main symptoms of Alzheimer disease and other dementias. Glycyrrhiza uralensis is a natural product that has a protective effect against cognitive impairment. In this study, we investigated whether glycyrrhizic acid, among the main bioactive components of <i>Glycyrrhiza uralensis</i>, has a neuroprotective effect on scopolamine-induced cognitive impairment.Methods: Twenty-week-old male Institute of Cancer Research mice were used in this study. The scopolam… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
11
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 28 publications
(11 citation statements)
references
References 33 publications
0
11
0
Order By: Relevance
“…As per animal ethics committee recommendations, all of the research animals were handled with care and empathy. The doses of scopolamine and friedelin were selected and optimized from the literature review [ 22 ]. Friedelin isolated from different plants had already been reported to have significant in vivo activities in animal models of hepatotoxicity [ 15 ], gastro-protective activities [ 12 ], and anti-inflammatory and antipyretic activities [ 23 ].…”
Section: Methodsmentioning
confidence: 99%
“…As per animal ethics committee recommendations, all of the research animals were handled with care and empathy. The doses of scopolamine and friedelin were selected and optimized from the literature review [ 22 ]. Friedelin isolated from different plants had already been reported to have significant in vivo activities in animal models of hepatotoxicity [ 15 ], gastro-protective activities [ 12 ], and anti-inflammatory and antipyretic activities [ 23 ].…”
Section: Methodsmentioning
confidence: 99%
“…Glycyrrhizic acid (GA), as a major component of Glycyrrhiza glabra roots, belongs to flavonoids, which exhibits antioxidant, anti-inflammatory, and antiexcitotoxic properties [108]. GA substantially increases the expression rate and 14 Oxidative Medicine and Cellular Longevity mass of mitochondrial genes subsequent to aluminum toxicity [109].…”
Section: Amla C2c12 Myotubesmentioning
confidence: 99%
“…DG can reduce TNF-α, NF-κB, IL-1, IL-6, and IL-17. [9][10][11] In addition, it increases the expression and activity of superoxide dismutase and catalase, 12 and decreases the production of nitric oxide synthase 13 and reactive oxygen species. 14 Previous studies have found these factors play important roles in the pathogenesis of rosacea.…”
Section: Discussionmentioning
confidence: 99%